Eczema as an adverse effect of anti-TNFα therapy in psoriasis and other Th1-mediated diseases: a review. (3rd April 2017) - Nakamura, Mio; Lee, Kristina; Singh, Rasnik; Zhu, Tian Hao; Farahnik, Benjamin; Abrouk, Michael; Koo, John; Bhutani, Tina
Abstract: Introduction: There have been rare reports of eczema occurring as an adverse effect of anti-tumor necrosis factor-alpha (TNFα) therapy. Methods: A literature search was conducted on PubMed for articles describing new onset or worsening of preexisting eczema during anti-TNFα therapy for the treatment of various inflammatory diseases. Results: Eczema as an adverse effect of anti-TNFα therapy may occur in approximately 5–20% of patients with various Th1-mediated inflammatory diseases such as psoriasis, inflammatory arthritis and inflammatory bowel disease. Personal history of atopy appears to increase this risk. Out of the anti-TNFα agents indicated for the treatment of moderate-to-severe psoriasis, infliximab may be more strongly associated with development or exacerbation of preexisting eczema. Discussion: Inhibitors of key mediators in the Th1 pathway such as TNFα are successful therapeutic targets for the treatment of various inflammatory conditions such as psoriasis, psoriatic arthritis, rheumatoid arthritis and inflammatory bowel disease. Blocking the Th1 pathway may create an imbalance favoring increased activity of the opposing Th2 pathway implicated in inflammatory conditions such as eczema. Further research is needed to better understand the role of the Th1/Th2 balance in various inflammatory diseases and how the immunologic environment is affected by immunotherapies.